Regional Economic Inactivity Trends in Poland (OECD Reviews on Local Job Creation, 2021)
Despite its rapid economic growth over the past decades, Poland's economic inactivity rate remains above the OECD average and regional differences in labour force participation persist. This report sheds light on the drivers of economic inactivity across Polish regions and analyses them in light of both individual and structural factors associated with labour force participation. It highlights the need for more inclusive active labour market policies to help integrate the economically inactive into labour markets across Poland. A better integration of services provided by national and local institutions, as well as a strengthened role of the social economy, is needed to address the complex needs of economically inactive persons